Growth of ultrahigh density single-walled carbon nanotube forests by improved catalyst design. - Zhong, G; Warner, J; Fouquet, M; Robertson, A; Chen, B; Robertson, J (2012)
We have grown vertically aligned single-walled carbon nanotube forests with an area density of 1.5 × 10(13) cm(-2), the highest yet achieved, by reducing the average diameter of the nanotubes. We use a nanolaminate Fe-Al(2)O(3) catalyst design consisting of three layers of Al(2)O(3), Fe, and Al(2)O(3), in which the lower Al(2)O(3) layer is densified by an oxygen plasma treatment to increase its diffusion barrier properties, to allow a thinner catalyst layer to be used. This high nanotube density is desirable for using carbon nanotubes as interconnects in integrated circuits.